Bacterial diversity associated with red seaweeds, gracilaria manilaensis & laurencia sp., found in Peninsular Malaysia - Najatul Su Ad binti Abdullah (Kulliyyah of Science, International Islamic University Malaysia, 2020)
Red seaweeds, Rhodophyta, are very beneficial as a good source of nutrients, collagen, and bioactive metabolites. Thus, seaweeds are consumed or harvested for various industries, including processed food and nutraceuticals. It has been debated that metabolic compounds of the seaweeds could be due to the interactions between the seaweeds and its holobiont environment which hosts microorganisms such as bacteria, protists, algal virus, fungi, and diatoms. It was the interest of this research to investigate the bacterial community profile of edible red seaweed, Gracilaria manilaensis, often found in coastal villages of peninsular Malaysia, and compare it against Laurencia sp., which is a genus prolific for the discovery and extraction of bioactive metabolic compounds. Studies of bacterial diversity associated to other Rhodophyta species have been conducted worldwide, but not extensively in Malaysia. Isolation of bacteria from marine environment is primarily done for identification of bacterial species and exploring the value of bacteria or its bioactive compounds in biotechnological application. Eight selective enrichment media were used and the bacteria isolated was also compared to the bacteria profile identified through amplicon sequencing. For the seaweed, G. manilaensis, there was a total colony count of 1022 on 8 media with 3 replicates, which 80 isolates were selected for 16S rRNA identification and 43 OTUs were identified. Dominant bacteria phylum was Proteobacteria, and other isolated phyla were Firmicutes, Bacteroidetes, and Actinobacteria. The phyla profile was similar to that of the amplicon sequencing sample with 88 OTUs identified. For the red seaweed, Laurencia sp., 8 OTUs were isolated by bacteria culture-dependent approach and 41 OTUs were discovered by amplicon sequencing molecular approach. From the 8 culture OTUs, 3 were positive from bromoperoxidase gene. Sequences data analysis indicated that members of the Alphaproteobacteria and the Bacteroidetes which are predominant were likely to have an important role in the function of this marine bacterial community as the bacterial phyla observed are ubiquitous in seawater with some OTUs and isolates were homologous to bacteria in marine host cluster. Further investigation on these bacteria is hoped to reveal how the identified bacteria can be beneficial in a seaweed environment or for other biodiscoveries.